“Our life has changed so much” :|researching COVID-19 phenomenon with first grade children - Dereli Özengen, Elif Kevser. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study attempts to investigate children's experiences with the COVID-19 pandemic. It is also aimed to be an intermediary for children to underline their competencies and make their voices heard with minimal adult interference by using the research with children method. Fourteen first-grade students in a private primary school in Istanbul, Turkey directed the study by working as co-researchers. The study is designed as a phenomenological case study. Since phenomenology studies aim to convey the experiences of individuals through their perspectives, the data consists of children's drawings, photographs, and individual and group interviews. The data is analyzed through thematic content analysis. As a result of the research, various findings are obtained about what children know about the COVID-19 phenomenon, the impact of the pandemic on their own and others' lives, their online and face-to-face education experiences, the factors that increase their resilience while staying at home, and their expectations from the authorities.
Keywords: COVID-19 (Disease) -- Study and teaching (Elementary)